Exploiting the synergic strengthening effects of stacking faults in carbon nanotubes reinforced aluminum matrix composites for enhanced mechanical properties. (15th April 2021) - Guo, Baisong; Song, Min; Zhang, Xinming; Liu, Yangzhen; Cen, Xi; Chen, Biao; Li, Wei
Abstract: Carbon nanotubes (CNTs) reinforced Al matrix composites containing high-density stacking faults were successfully fabricated through spark plasma sintering (SPS) and subsequently hot rolling with high strain rate. It is found that the inclusion of CNTs facilitate the formation of stacking fault in Al matrix. With increasing the CNTs from 0.5 vol% to 1.0 vol%, the density of stacking fault increases, which is mainly because of the reduced stacking fault energy of Al matrix in Al/CNTs composites, as revealed by the density functional theory simulation. Combined with the effective exploitation of the strengthening effectiveness of CNTs due to uniform dispersion of CNTs and well bonded Al-CNTs interface, the highest tensile strength (378 ± 8 MPa) together with good ductility (17.1 ± 1.5%) can be achieved for 1 vol% CNTs reinforced Al matrix composite. Moreover, the enhanced strength deriving from each strengthening mechanism relies on the CNTs content. When the CNTs content is 1.0 vol%, Orowan looping and stacking fault strengthening are the dominant strengthening mechanisms. The reported microstructure design and control can be informative for improving the mechanical properties of CNTs reinforced metal matrix composites. Graphical abstract: Image 1 Highlights: Stacking faults were included into carbon nanotubes reinforced aluminum matrix composites. The combined strengthening effects of carbon nanotubes and stacking faults were investigated. The improved strength of fabricated composites can be achieved without obvious loss of ductility. The reasons for forming stacking faults in present composites were elucidated. The strength contribution from the involved strengthening mechanisms were discussed.